Food lipids chemistry, nutrition, and biotechnology - Akoh, Casimir C. 1955- (Boca Raton CRC Press, 2017)
"Maintaining the high standards that made the previous editions such well-respected and widely used references, Food Lipids: Chemistry, Nutrition, and Biotechnology, Fourth Edition provides a new look at lipid oxidation and highlights recent findings and research. Always representative of the current state of lipid science, this edition provides 16 new chapters and 21 updated chapters, written by leading international experts, that reflect the latest advances in technology and studies of food lipids"--Provided by publisher.
Keywords: Lipids; Lipids in human nutrition; Lipids -- Biotechnology; Lipids -- Metabolism